Analysis of lymphatic and blood vessel invasion biomarkers in T1 esophagogastric adenocarcinomas for improved patient prognostication. Issue 3 (1st April 2015) - Perry, C.; Soomro, I.; Kaye, P.; Hardy, E.; Parsons, S. L.; Ragunath, K.; Lobo, D. N.; Martin, S. G.; Madhusudan, S.
Summary: Lymphovascular invasion (LVI) in T1 esophagogastric adenocarcinoma may predict risk of recurrence despite definitive treatment with surgery or endoscopic resection. Podoplanin and CD34 are emerging biomarkers of lymphatic and blood vessel invasion, respectively, and could be adopted to refine LVI assessment. A consecutive series of 65 patients with T1 adenocarcinomas diagnosed at Nottingham University Hospitals were investigated. T1 tumors from 43/65 patients who received primary surgery only were suitable for LVI evaluation by hematoxylin and eosin (H&E) staining as well as by CD34 and Podoplanin immunohistochemistry. LVI was correlated to clinicopathological features and recurrence free survival. H&E staining detected LVI in 11.6% (5/43) of T1 tumors. CD34 and Podoplanin immunohistochemistry significantly improved LVI detection to 25.6% (11/43). Compared with LVI by H&E, immunohistochemical evaluation of blood vessel invasion (CD34) or lymphatic vessel invasion (Podoplanin) was significantly associated with higher grade ( P = 0.005), submucosal invasion (T1b) ( P = 0.018), lymph node positivity (N1) ( P = 0.029) and poor recurrence free survival ( P = 0.0003). Our study provides evidence that CD34 and Podoplanin immunohistochemistry could improve LVI detection and allow better prognostication of patients and optimum selection of definitive treatment. Larger multicenter studies are required for further validation that could have significant clinical implications.